The Magic Porridge Pot - Illustrated by Barella, Laura (London Ladybird Books)
The porridge pot always produces food for the little girl, but it runs amuck when her mother tries to use it without knowing the magic words to stop it.
Include Color Illustrations
Keywords: Magic -- Children's stories